Avant-garde art in everyday life : early twentieth-century European Modernism - Witkovsky, Matthew S.; Ash, Jared (New Haven, Conn. ; London : Yale University Press, 2011)
Beginning around 1910, vanguard artists demanded that true art go beyond the intellectual and transform daily life. This title highlights the work of six influential European artists who took this idea into the wider world, where it merged enthusiastically with demands in the industrial marketplace, nascent mass media, and urban popular culture.
Contents: John Heartfield / Andrés Mario Zervigón -- Gustav Klutsis / Jared Ash -- El Lissitzky / Maria Gough -- Ladislav Sutnar / Jindřich Toman -- Karel Teige / Matthew S. Witkovsky -- Piet Zwart / Nancy J. Troy.
Published in conjunction with an exhibition held at the Art Institute of Chicago, June 11-Oct. 9, 2011.
boek